Antifungal activity in vitro of Sapranthus microcarpus (Annonaceae) against phytopathogens - de-la-Cruz-Chacón, Iván; López-Fernández, Nora Yazmin; Riley-Saldaña, Christian Anabí; Castro Moreno, Marisol; González-Esquinca, Alma Rosa (Instituto de Ecología, A.C., 2018)
Background and Aims: The phytochemistry study of Annonaceae has intensified in the last decades due to the discovery of secondary metabolites with antimicrobial activities. The inhibitory activities of extracts and compounds from these species for phytopathogens are less known. The antifungal activity of Sapranthus microcarpus was determined in vitro against six fungal pathogens of important crops.Methods: Hexane, methanol, and alkaloid extracts of the leaves and root and stem bark of S. microcarpus were evaluated to determine whether they could inhibit the mycelial growth of the phytopathogens. The combined activity of the most active extracts for each phytopathogen was also determined. The alkaloid liriodenine was isolated and identified as an antifungal principle.Key results: All extracts inhibited the growth of the six phytopathogens to some extent. The root bark alkaloid extract showed the highest activity. Fusarium oxysporum f. sp. lycopersici and Curvularia lunata were the most sensitive phytopathogens. Liriodenine was active against all the plant pathogens (minimum inhibitory concentrations of 125-500 nmol ml-1).Conclusions: Sapranthus microcarpus is a native natural resource with great phytochemical potential.